EVALUATION OF MONERO COIN MINING PROJECT FOR TWO YEARS PERIOD USING REAL OPTIONS WITH LEARNING PROCESS - Aldi Susanto, Richard
Cryptocurrency mining project is a complex investment as it depends on several factors such as cryptocurrency price fluctuations. In this final project, monero coin mining for a two-year period will be evaluated by real options with learning process. Monero coin, as a type of cryptocurrency with high price fluctuations, is potential to be evaluated since the value of real options depends on the underlying asset volatility. The project valuation using real options with learning process will be evaluated by Guthrie’s binomial method and Haahtela’s trinomial method. Project valuation by implementing real options with learning process has a positive impact on project net present value. Evaluation of the monero coin project value using real options with learning process could be a reference for investors to optimize their investment on monero coin mining project.